2022
DOI: 10.1001/jamanetworkopen.2022.6822
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Risk Factors Associated With Poor Humoral Immune Response of SARS-CoV-2 Vaccines in Recipients of Solid Organ Transplant

Abstract: Key Points Question What are the humoral immune response rates and risk factors associated with diminished response after COVID-19 vaccination in recipients of solid organ transplant? Findings In this systematic review and meta-analysis of 29 studies and 11 713 recipients of solid organ transplant, seroconversion rates increased with progressively increased numbers of mRNA COVID-19 vaccine doses. Older age, recent transplantation, deceased donor status, act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(136 citation statements)
references
References 121 publications
(664 reference statements)
9
112
5
1
Order By: Relevance
“…In general, the studies showed that patients with chronic kidney failure on dialysis (not requiring organ transplantation) [ 10 , 11 , 12 ], immune-mediated inflammatory diseases [ 13 , 14 , 15 , 16 ], and solid tumors [ 17 ] had seroconversion rates that were high and similar to healthy controls (seroconversion rates among patients ranged from about 83% to 97%). In contrast, patients with receipt of anti-CD20 therapy [ 18 ] and solid organ transplants [ 11 , 19 , 20 ] (thus requiring anti-rejection immunosuppression) had markedly low vaccine seroconversion rates (rates ranged from about 26% to 45% after two vaccine doses). Patients with hematologic cancers had intermediate seroconversion rates (rates ranged from about 54% to 65%) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the studies showed that patients with chronic kidney failure on dialysis (not requiring organ transplantation) [ 10 , 11 , 12 ], immune-mediated inflammatory diseases [ 13 , 14 , 15 , 16 ], and solid tumors [ 17 ] had seroconversion rates that were high and similar to healthy controls (seroconversion rates among patients ranged from about 83% to 97%). In contrast, patients with receipt of anti-CD20 therapy [ 18 ] and solid organ transplants [ 11 , 19 , 20 ] (thus requiring anti-rejection immunosuppression) had markedly low vaccine seroconversion rates (rates ranged from about 26% to 45% after two vaccine doses). Patients with hematologic cancers had intermediate seroconversion rates (rates ranged from about 54% to 65%) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Patients with hematologic cancers had intermediate seroconversion rates (rates ranged from about 54% to 65%) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. An intervention that improved vaccine efficacy was the use of additional booster vaccine doses [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary objective was to make a comparative present less robust immune responses than nontransplant patients [13]. Studies have found a reduced humoral immune response to BNT162b2 and mRNA-1273 mRNA vaccines in SOTRs after the first and second doses, measured by antispike antibody responses [14,15] in kidney [16], lung [17], heart [18,19], liver [20], and in general in SOTRs [15], who are underrepresented in clinical trials. However, many immunosuppressed patients and patients with other comorbidities have already been vaccinated with up to four doses in many countries, and few prospective studies have been specifically designed to target these patients.…”
Section: Active Surveillance Programmentioning
confidence: 99%
“…While measures to curb the spread of SARS-CoV-2, a pathogen that has claimed the lives of more than a million Americans, continue to ease in many parts of the United States, the risk of adverse outcomes related to infection in immunocompromised hosts remains substantial 1,2 . In a recent meta-analysis that included nearly 12,000 solid organ transplant (SOT) recipients, vaccination against COVID-19 elicited a humoral response that was signi cantly reduced compared to that of immunocompetent hosts 3 . Though vaccination results in a markedly decreased risk of severe infection in the immunocompetent majority, a diminished response to vaccination translates to a greater risk of severe disease and death in SOT recipients 4 .…”
Section: Introductionmentioning
confidence: 99%